Factors Influencing Purchase of Advanced Intelligent Driving Vehicles in China: A Perspective of Value-Based Adoption Model - Yanlu Yang; Yiyuan Wang; Xiaohan Bi (World Electric Vehicle Journal)
Although Chinese consumers show an increasing acceptance of intelligent driving, their purchase intentions have declined. Advanced intelligent driving technologies play a crucial role in helping users transition from traditional driving to fully autonomous driving. However, low purchase intention may delay the market adoption of advanced intelligent driving technologies, further influencing the research and innovation of autonomous driving technology. This study, from the perspective of consumer perception, collected survey data and constructed a structural equation model to explore the mechanisms by which key variables—such as perceived usefulness, perceived enjoyment, perceived fee, perceived risk, and brand credibility—affect consumers’ purchase intentions. The results indicate that perceived usefulness and perceived enjoyment significantly enhance consumers’ perceived value. In contrast, perceived fee negatively impacts perceived value. Unlike previous studies, perceived risk does not have a significant impact on perceived value in the current stage of advanced autonomous driving. Perceived value has a significant positive impact on purchase intention, confirming its central role in consumer behavior models. Moreover, brand credibility significantly affects purchase intention but does not have a notable influence on perceived value.